PENGEMBANGAN MEDIA PEMBELAJARAN UNO STACKO BACA PADA PEMBELAJARAN IPS KELAS IV SEKOLAH DASAR - Devita Luluanna; Eddy Noviana; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was motivated by the finding of the fact that many social teachers teach social studies using the lecture method only, do not vary and do not involve students to learn more actively. It makes students are unmotivated and bored in learning social studies. To overcome these problems, teachers must be able to create fun learning method such as by making social studies learning media. This research aims to determine whether the developed media, namely Uno Stacko Baca, is suitable to be used for fourth grade elementary school students. This research refers to the R&D method with a modified 4D development model into three stages, such as the definition stage, the design stage and the development stage. The results of this research showed that the developed media was feasible to be tested with a score of 78.57% for media assessment and 82% for material assessment. The media was also very feasible as a learning media with a score of 96.67% from the practitioner's response to 90.78% of student responses in the small group test. Key Words: Learning Media; Uno Stacko Baca, Social Studies